Faktor Determinan yang berhubungan dengan Kepuasan Kerja Perawat Pelaksana di Rsud Dr. Rasidin Padang - Erni Musmiler; Yulastri Arif; Wawan Wahyudi (Jurnal Akademika Baiturrahim Jambi, 2020)
Job satisfaction of nurses need serious attention because nurses care provider with the largest and longest time to patients. The achievement of hospitals BOR is low (26.20%) that be caused the result of achievement of the performance of nurses are not optimal yet, this is caused to the dissatisfaction of nurses to hospitals management. The aim of this research is to find determinant factors that related to job satisfaction of nurses executive in RSUD dr. Rasidin Padang. This research is know deskriptive correlation with cross sectional to 72 executive nurses in RSUD dr. Rasidin. Instrument of the research is questionnaire. Univariate data analysis used frequency distribution, bivariate with chi square test, and multivariate used logistic regression test. The result of the research is 51.4% executive nurses state dissatisfaction in working. Chi-square test is obtained there is significant correlation between the incentive, promotion opportunity, and supervision with job satisfaction. There is not correlation between the leadership, and work environment condition with job satisfaction. The result of multivariate analysis is obtained variable incentive that is dominant factors related to job satisfaction of nurses. It is expected the stakeholders of hospital management to consider the burned and risk of work based on objective performance assesment, the setting of level system performance-based on achievement career. Running the monitoring system to nursing care is given by executive nurses, and immediately to do accreditation of hospital to improve the quality of hospital services.